Corrigendum to "G2 B-spline interpolation to a closed mesh" [Comput Aided Des 43 (2011) 145–160]. (February 2015) - Lu, Yang; Shi, Kan-Le; Yong, Jun-Hai; Zhang, Sen; Song, Hai-Chuan
Abstract: A G 2 interpolation method to a closed mesh was proposed by Shi et al. in [1]. This note points out that their method has two theoretical defects, which may lead to the failure of G 2 continuity. We fix these defects and correct several formula mistakes.